Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s44251-023-00026-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of graphitic carbon nitride: doping and plasmonic effect, and photocatalytic applications

Pradeepta Babu,
Hyewon Park,
Jeong Young Park

Abstract: To achieve the United Nations' Sustainable Development Goal (SDG7) of limiting global temperature rise to less than 1.5 °C, it is crucial to reduce non-renewable energy sources and curb the production of greenhouse gases like CO2. In this context, graphitic carbon nitride (g-C3N4) has emerged as a promising metal-free semiconductor photocatalyst for converting solar energy into clean fuels and valuable chemicals. However, there are challenges associated with g-C3N4, such as high electron–hole recombination, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 347 publications
0
1
0
Order By: Relevance
“…Elemental doping is a common strategy to manipulate the charge transport properties of intrinsic semiconductors . The doping process increases the ability of materials to absorb visible light by distributing the HOMO and LUMO and preventing recombination centers as well as creating inherent semiconducting behavior . For instance, Biswas et al reported increased photoactivity of a visible-light responsive W-doped FeVO 4 photoanode …”
Section: Energy Harvesting Materialsmentioning
confidence: 99%
“…Elemental doping is a common strategy to manipulate the charge transport properties of intrinsic semiconductors . The doping process increases the ability of materials to absorb visible light by distributing the HOMO and LUMO and preventing recombination centers as well as creating inherent semiconducting behavior . For instance, Biswas et al reported increased photoactivity of a visible-light responsive W-doped FeVO 4 photoanode …”
Section: Energy Harvesting Materialsmentioning
confidence: 99%